Possibilities of mathematical problems in logical thinking. Development of secondary education pupils - Bakhyt, Sydykhov; Kalimbetov, Burkhan; Khabibullayev, Zhanibek (Opción, 2019)
In the article pedagogical prerequisites are considered for the performance by younger school students of the system of assignments in mathematics as a method of forming logic acknowledges skills and means of the practical study of logical concepts. As a method, circular schemes, models of real objects and verbal descriptions of logical relationships are used without reliance on visual models at three different levels. As a conclusion, junior schoolchildren are convinced that the process of learning and cognition is not limited by lessons and textbooks of mathematics, they permeate their entire life.